(untitled) (Revista Electrónica REDINE, 2025)
The purpose of this inquiry was to identify the various learning difficulties experienced by university students when taking the Research Methodology course in different majors or degree programs. To this end, a documentary research study was conducted, based on the principles of the qualitative approach and grounded in the characteristics of the interpretive paradigm and the hermeneutic method. Fifteen articles published in scientific journals were reviewed. The Google search engine and the Perplexity Artificial Intelligence tool were used for the research. A systematization process was then carried out, which allowed for the establishment of four main categories that emerged from the collected information and its corresponding interpretation: “Meanings of concepts and methodological definitions,” “Methodological conflicts,” “Affective and motivational barriers,” and “Digital and virtual challenges.” Among the conclusions, it was highlighted that the teaching and learning process in the subject of Research Methodology must be comprehensive. This is because it is important to integrate theoretical and practical aspects, writing skills, ongoing teacher training and professional development, and the integration of teacher and student activities to provide cognitive and affective support. It is also crucial to understand the importance of scientific inquiry and the ethical considerations that must be present when conducting research. Furthermore, the curriculum should incorporate content linked to learning based on problem-solving, digital interaction, and gamification to achieve engaging and enjoyable participation, among other elements.